(untitled) (Orfeu, 2023)
This study aimed to investigate the experience of the Covid-19 pandemic, from March 2020 to early 2021, by experimental music artists, and festival and concert venue curators in Portugal, and their adaptation processes during this period. For this purpose, interviews were undertaken with 8 artists and/or programming directors linked to the experimental music context, and the resulting data was analysed to identify relevant topics and transversal themes. Despite the existence of often-insoluble obstacles to artistic practice, all venues and events maintained a significant level of activity, emphasizing the use of digital means of communication and dissemination as the most common alternative. However, some communication problems with the public resulting from these options were also mentioned, as well as the negative impact both on the identity of these entities and on the artists’ professional sustainability.